Exogenous Hydrogen Sulfide Enhanced Antioxidant Capacity, Amylase Activities and Salt Tolerance of Cucumber Hypocotyls and Radicles - YU, Li-xu; ZHANG, Cun-jia; SHANG, Hong-qin; WANG, Xiu-feng; WEI, Min; YANG, Feng-juan; SHI, Qing-hua (Journal of Integrative Agriculture, 2013)
In the present experiment, effects of sodium hydrosulfide （NariS）, a H2S donor, on the oxidative damage, antioxidant capacity and the growth of cucumber hypocotyls and radicles were studied under 100 mmol L^-1 NaCl stress. NaCl treatment significantly induced accumulation of H2O2 and thiobarbituric acid-reactive substances （TBARS） in cucumber hypocotyls and radicles, and application of NariS dramatically reduced the accumulation of H/O2 and lipid peroxidation. However, the alleviating effects greatly depended on the concentrations of NariS, and 400 ~tmol L-1 NariS treatment showed the most significant effects. Corresponding to the change of lipid peroxidation, higher activities of antioxidant enzymes as well as the antioxidant capacity indicated as DPPH scavenging ac＇tivity, chelating activity of ferrous ions and hydroxyl radical （.OH） scavenging activity were induced by Naris treatment under NaCI stress, especially by 400 Ixmol L-I Naris treatment. With the alleviating lipid peroxidation, the amylase activities in cotyledons were increased, and the length of cucumber hypocotyls and radicles were significantly promoted by NariS treatment under NaCI stress. Unlike the effects of NariS, pretreatment with other sodium salts including Na2S, NazSO4, NaHSO4, Na2SO3, NaHSO3 and NaAc did not show significant effects on the growth of cucumber hypocotyls and radicles. These salts do not release H2S. Based on above results, it can be concluded that the effects of NariS in the experiment depended on the H2S rather than other compounds derived from NariS, and the alleviating effects might related with its function in modulating antioxidant capacity and amylase activities.